2013
DOI: 10.1017/s0021859613000129
|View full text |Cite
|
Sign up to set email alerts
|

A modified method for assessment of the morphological stage of development as a predictor of alfalfa herbage chemical composition and nutritive value

Abstract: The aim of the current work was to investigate the possibility of modifying the existing mean stage by weight (MSW) system for evaluating the average development stage in alfalfa. The modification was performed with the aim of providing a simplified system that may be used to evaluate the alfalfa development stage and to predict its nutritive value for ruminants. The suggested modification consists of designating an MSW value on the basis of the fresh weight of all morphological stages in a fresh green plant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Stage of maturity at the time of harvest is considered to be one of the most important factors affecting forage chemical composition of lucerne (Hakl et al ., ; Božičković et al ., ). Within a dense stand, the competition for light between plants produces a decrease in leaf and stem N concentration (Lemaire et al ., ), which is consistent with reduced CP concentration of plant parts and increased MSL from bud to flower stage in the present experiment.…”
Section: Discussionmentioning
confidence: 97%
“…Stage of maturity at the time of harvest is considered to be one of the most important factors affecting forage chemical composition of lucerne (Hakl et al ., ; Božičković et al ., ). Within a dense stand, the competition for light between plants produces a decrease in leaf and stem N concentration (Lemaire et al ., ), which is consistent with reduced CP concentration of plant parts and increased MSL from bud to flower stage in the present experiment.…”
Section: Discussionmentioning
confidence: 97%
“…According to Božičković et al (2013), there were no statistically significant differences between MSW and MSFW when calculated on the same sample, while correlation between these two values was very strong ( r > 0.99). Also, Božičković et al (2013) suggested that for prediction of MSFW on the basis of measured MSW, the equation developed from the first three growth cycles, Eq. [4], should be used: MSFWpredicted = 0.9808 × MSW…”
mentioning
confidence: 85%
“…Our previous investigation (Božičković et al, 2013) showed that it is possible to obtain an accurate MSW value without drying. The difference of the new approach from the original methodology is that the fresh weight was used to obtain the mean stage of development.…”
mentioning
confidence: 99%
“…The detailed sampling procedure was given by Božičković et al (2012;2013). During 2010, on the same alfalfa field a total of 141 fresh samples were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Because of all that, the adequate evaluation of optimal moment for cutting can be conducted only with the data about chemical composition and nutritive value of alfalfa. For that estimation, different methods can be utilized: mean stage of development (Kalu and Fick, 1981;Božičković et al, 2013) and method according to Hintz and Albrecht (1991). It is also possible to use the Near-infrared spectroscopy (NIRS).…”
Section: Growth Cyclementioning
confidence: 99%